Effectiveness of Psychosocial and Clinical Interventions to Improve Psychological Well-Being in Older Adults: A Systematic Review - Desi Novitasari; Retno Indarwati; Rista Fauziningtyas (Jurnal Ners, 2026)
Introduction: Older adults are prone to decreased psychological well-being due to biological, social, and emotional changes. Non-pharmacological interventions offer alternative approaches to improving mental health in older adults. Methods: This systematic review analysed nine RCTs of intervention studies published between 2022–2024. The study evaluated the effectiveness of various interventions such as mindfulness, reminiscence therapy, virtual reality, and community social support. Results: Most studies (n = 9) eported improvements in psychological well-being, spirituality, and quality of life, as well as a decrease in symptoms of depression and anxiety. Community-based and self-reflective interventions such as life story reviews and Mindfulness-Based Elder Care (MBEC) howed significant results. Social support and psychological empowerment have proven to be important mediators of intervention success. Conclusions: Non-pharmacological interventions have great potential in improving the well-being of older adults. Further comprehensive and ongoing research is needed to ensure long-term effectiveness. Keywords: awareness; memory therapy; non-pharmacological interventions; psychological well-being; social support.